Comparing the Vocabulary Learning Strategies of High School and University Students: A Pilot Study - Dóczi, Brigitta (Working Papers in Language Pedagogy, 2011)
The pilot study described in this paper aims to investigate the role of Vocabulary Learning Strategies (VLS) in Hungarian secondary and tertiary educational institutions. It intended to explore the strategies students apply in the final year of high school and 3 different years of university. The first part of the paper summarizes the most significant issues and research studies in the field of VLS. Following this, it describes the study itself, for the purpose of which a questionnaire was devised, based on Schmitt’s (1997) taxonomy. As the findings show, social and metacognitive strategies are less frequently used by the participants. The higher the number of years of study, the less students pratise on a regular basis or use active strategies. However, they are more likely to skip a new word and they pay more attention to pronunciation. As regards the number of strategies used, it increases with time spent studying the language.